2001
DOI: 10.1053/jlts.2001.20784
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of vancomycin-resistant enterococcal colonization in liver and kidney transplant recipients

Abstract: T he natural history of vancomycin-resistant enterococcus (VRE) infection is such that VRE colonization, predominantly of the gastrointestinal tract, typically precedes infection. At Mayo Medical Center (Rochester, MN), routine aerobic bacterial throat, rectal, wound, biliary, and urinary surveillance cultures have been collected from liver transplant recipients as part of a selective bowel antibiotic decontamination program for liver transplant patients. Beginning in 1995, as a result of these surveillance cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
70
2
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 16 publications
3
70
2
2
Order By: Relevance
“…VRE has emerged as an important pathogen in liver, kidney, and SCT units in the United States. [4][5][6][7][8]20 Colonization with VRE has been reported in as many as 50% of pediatric oncology patients. 17 At present, there are very limited data with regard to the incidence and clinical consequences of VRE in pediatric SCT patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VRE has emerged as an important pathogen in liver, kidney, and SCT units in the United States. [4][5][6][7][8]20 Colonization with VRE has been reported in as many as 50% of pediatric oncology patients. 17 At present, there are very limited data with regard to the incidence and clinical consequences of VRE in pediatric SCT patients.…”
Section: Discussionmentioning
confidence: 99%
“…3 Immune compromised patients, especially adult liver, kidney, and pancreatic transplant patients, have experienced serious morbidity and mortality as a consequence of VRE. [4][5][6][7][8] The first reported case of VRE bacteremia in a bone marrow transplant recipient was described in 1991. 9 Recent reports in adult stem cell transplant (SCT) patients have shown that VRE bacteremia results in significant complications and fatalities.…”
mentioning
confidence: 99%
“…Data on duration of VRE colonization indicate that colonization may be prolonged, with high rates of relapse after multiple consecutive negative surveillance cultures. [14][15][16] Factors associated with prolonged VRE carriage include immunocompromising conditions and concomitant antibiotic exposure. [16][17][18][19] Additionally, patients with diarrhea and uncontrolled respiratory secretions and draining wounds may pose the highest risk for transmission in the healthcare environment.…”
Section: Vancomycin-resistant Enterococci (Vre)mentioning
confidence: 99%
“…12,60 Some studies have included surveillance cultures obtained from other sites including throat and urine samples. 16 While limited, data comparing the sensitivity of rectal and perirectal cultures suggest that both are comparable. 74 …”
Section: Sites Of Colonizationmentioning
confidence: 99%
See 1 more Smart Citation